2014
DOI: 10.18632/oncotarget.1963
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin promotes pancreatic cancer progression by inhibiting apoptosis via the activation of AMPK/Sirt1/PGC-1α signaling

Abstract: Adiponectin is an adipocyte-secreted adipokine with pleiotropic actions. Clinical evidence has shown that serum adiponectin levels are increased and that adiponectin can protect pancreatic beta cells against apoptosis, which suggests that adiponectin may play an anti-apoptotic role in pancreatic cancer (PC). Here, we investigated the effects of adiponectin on PC development and elucidated the underlying molecular mechanisms. Adiponectin deficiency markedly attenuated pancreatic tumorigenesis in vivo. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 53 publications
5
62
0
Order By: Relevance
“…In our study, adiponectin level resulted in an independent predictor both for death and disease progression. This is in agreement with recent in vivo studies (48) showing that, unlike most other cancers, adiponectin deficiency significantly alleviate pancreatic cancer growth and metastasis. This unconventional role of adiponectin in the promotion of pancreatic cancer progression could be explained by its potent antiapoptotic effects via the activation of AMPK/Sirt1/PGC1a signaling (48).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, adiponectin level resulted in an independent predictor both for death and disease progression. This is in agreement with recent in vivo studies (48) showing that, unlike most other cancers, adiponectin deficiency significantly alleviate pancreatic cancer growth and metastasis. This unconventional role of adiponectin in the promotion of pancreatic cancer progression could be explained by its potent antiapoptotic effects via the activation of AMPK/Sirt1/PGC1a signaling (48).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, the mortality rates of the adiponectin-deficient mice with sarcomas were lower than the rates of the WT control mice ( Figure 2B). These results were consistent to our previous findings that adiponectin deficiency suppressed pancreatic cancer [7]. In spite of this, the exact roles of adiponectin in cancers are controversial and need further study.…”
Section: Discussionsupporting
confidence: 92%
“…Many reports demonstrated that adiponectin has regulatory effects on the development and progression of various tumors via different signaling pathways [4][5][6]. Our previous studies also explore the potential mechanism of adiponectin on pancreatic cancer [7]. However, the roles of adiponectin in sarcomas remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study conducted in adiponectin transgenic mice showed that elevated levels of adiponectin do not protect against CRC development (46). Third, emerging evidence has demonstrated that adiponectin exerts potent anti-apoptotic effect via activation of the AMPK/Sirtuin 1 (SIRT1)/PGC-1α pathway, leading to increased mitochondrial gene expression and cell proliferation (19). Lastly, adiponectin has been associated with a lower risk of development of fatty liver (47).…”
Section: Discussionmentioning
confidence: 99%